Immune Aspects of Biopharmaceuticals and Nanomedicines 2019
DOI: 10.1201/b22372-5
|View full text |Cite
|
Sign up to set email alerts
|

Current Understanding of Interactions between Nanoparticles and the Immune System

Abstract: The delivery of drugs, antigens, and imaging agents benefits from using nanotechnology-based carriers. The successful translation of nanoformulations to the clinic involves thorough assessment of their safety profiles, which, among other endpoints, includes evaluation of immunotoxicity. The past decade of research focusing on nanoparticle interaction with the immune system has been fruitful in terms of understanding the basics of nanoparticle immunocompatibility, developing a bioanalytical infrastructure to sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 77 publications
0
24
0
Order By: Relevance
“…The interaction between nanoparticles and immune system may involve both the innate and adaptative immune responses. As far as the innate immunity is concerned, several in vitro and in vivo studies show that exposure to ENM results in inflammation, characterized by inflammasome activation and induction of proinflammatory cytokines (Castranova, Schulte, & Zumwalde, 2013;Dobrovolskaia, Shurin, & Shvedova, 2016;Palomäki et al, 2011). Probably, however, ENM are not proinflammatory by themselves, but may induce inflammation if they aggregate/agglomerate and form larger particles easily recognized by phagocytes (Geiser, 2010), or if they adsorb on their surface bacterial products such as LPS, which are strong inducers of inflammation (Li & Boraschi, 2016).…”
Section: Immunotoxicity and Sensitizationmentioning
confidence: 99%
“…The interaction between nanoparticles and immune system may involve both the innate and adaptative immune responses. As far as the innate immunity is concerned, several in vitro and in vivo studies show that exposure to ENM results in inflammation, characterized by inflammasome activation and induction of proinflammatory cytokines (Castranova, Schulte, & Zumwalde, 2013;Dobrovolskaia, Shurin, & Shvedova, 2016;Palomäki et al, 2011). Probably, however, ENM are not proinflammatory by themselves, but may induce inflammation if they aggregate/agglomerate and form larger particles easily recognized by phagocytes (Geiser, 2010), or if they adsorb on their surface bacterial products such as LPS, which are strong inducers of inflammation (Li & Boraschi, 2016).…”
Section: Immunotoxicity and Sensitizationmentioning
confidence: 99%
“…Nanoparticles provide unique opportunities and challenges for cancer therapy and diagnosis. They have the potential to interact with the immune system and solid tumor microenvironment (TME) in unexpected ways to ultimately and critically affect performance and tumor response (1)(2)(3). The premise that nanoscale materials can be engineered to selectively detect and destroy cancer cells in solid tumors is undergoing a critical reevaluation (4)(5)(6)(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…These xenograft tumor studies rely on immunodeficient animal models, which provide a permissive environment for cross-species tissue grafting. Therefore, how well these models predict the potential and mechanisms for "nano-targeting" becomes a relevant question when the construct itself demonstrates strong interactions with the recipient's immune system (1)(2)(3)6).…”
Section: Introductionmentioning
confidence: 99%
“…Nanotechnology offers a substantial number of benefits over traditional routes for drug delivery, but unfavorable immune responses and liver accumulation have also been reported (Buzea, Pacheco, & Robbie, 2007;Zolnik, Gonzalez-Fernandez, Sadrieh, & Dobrovolskaia, 2010). It has been suggested that the adverse effects were elicited by numerous physicochemical characteristics, including size, shape, surface chemistry, or hydrophobicity (Dobrovolskaia, 2015;Dobrovolskaia, Shurin, & Shvedova, 2016). Engineering these properties with precision and homogeneity is a common strategy to improve the in vivo performance of nanomaterials.…”
Section: Physicochemical Properties Of Rna Nanoparticles Affect In mentioning
confidence: 99%